TUNING PARAMETER PID DENGAN METODE CIANCONE PADA PLANT HEAT EXCHANGER - MURIE DWIYANITI1; Kendi Moro (Politeknik Negeri Jakarta, 2013)
ABSTRACT Tuning of pid parameters is crucial in determining the success of a controller. But it is not easy to tune, some systems use a trial and error method that takes a long time to get the appropriate parameters. The purpose of this research is to provide a simple method of how to determine the pid parameters for controlling a process plant using ciancone’s method. This method is based on changes in plant reaction if given the input and the output response of the system is used as the basis to create a mathematical model with first-order approach. Then calculate the fraction dead time and determine the value of pid parameters based on correlation graphs ciancone. The results proved that the method is successful in controlling the temperature of the heat exchanger plant with pid parameter kc = 0.9, 1/ti = 1/28.08, and td = 2.16. With these parameters, the temperature of the plant heat exchanger can achieve the set point with rise time 21.9 seconds, settling time 101 seconds, 2.27 % overshoot and steady state error 0 . Furthermore, the system successfully follows the changes in set point and when given disturbance, the system can return to a steady state within 150 seconds. Key words : tuning , pid , ciancone method , heat exchanger. ABSTRAK Tuning parameter pid merupakan hal yang sangat penting dalam menentukan kerberhasilan sebuah pengendali. Namun untuk melakukan tuning tidaklah mudah, beberapa sistem menggunakan metode trial and error yang memerlukan waktu lama untuk mendapatkan parameter yang sesuai. Tujuan penelitian ini adalah memberikan metode yang sederhana bagaimana menentukan parameter pid untuk mengendalikan sebuah proses plant berdasarkan metode ciancone. Metode ini didasarkan pada perubahan reaksi plant jika diberi input dan respon keluaran sistem tersebut dijadikan dasar untuk membuat pemodelan matematika dengan pendekatan orde satu. Lalu menghitung fraction dead time dan menentukan nilai parameter pid berdasarkan grafik ciancone correlation. Hasil yang didapat terbukti bahwa metode ini berhasil mengendalikan suhu pada plant heat exchanger dengan parameter pid kc = 0.9, 1/ti = 1/28.08, dan td = 2.16. Dengan parameter tersebut, suhu pada plant heat exchanger dapat mencapai set point dengan rise time 21.9 detik, settling time 101 detik, overshoot 2.27% dan error steady state 0. Sistem juga berhasil mengikuti perubahan set point dan ketika terjadi gangguan, sistem dapat kembali ke keadaan steady state dalam waktu 150 detik. Kata kunci : tuning, pid, metode ciancone, heat exchange